Quantitative release assessment for beta-lactamase-producing Escherichia coli of dairy origin into vegetables - Kohei Makita; Dongsheng Zhang; Ayaka Okamura; Akira Fukuda; Natsumi Tokunaga; Tetsuo Asai; Yoko Shimazaki; Masaru Usui (CABI, 2024)
Abstract Outbreaks of food poisoning associated with vegetables contaminated with Escherichia coli have been reported globally. This study was conducted to assess the probability of releasing beta-lactamase-producing E. coli of dairy farm origin into vegetables in Japan. A release assessment model connecting dairy farms to vegetable farms was developed. Data on the indicated diseases and antimicrobial use in dairy cattle were obtained from the agricultural insurance program in Hokkaido Prefecture between 2016 and 2019. Data on bla-harboring E. coli in cattle were obtained from the Japan Veterinary Antimicrobial Resistance Monitoring System. Microbiological field sampling was conducted at dairy and vegetable farms. Inoculation experiments in vegetables were conducted. All processes in the model simulation were iterated for 1000 times. The estimated proportion of dairy farms holding cattle with bla-harboring E. coli was 6.00% (95% CI: 4.81-7.35%). Beta-lactams were used in 71.76% (333,098/464,204 average annual cases) of indicated diseases. The estimated concentration of bla-harboring E. coli in mixed fresh manure at affected farms was 3.33 log10 CFU/g (95% CI: 3.33-3.34). The concentrations were reduced to 0.83 (95% CI: 0.34-1.25) and −0.54 log10 CFU/g (95% CI: −1.04 to −0.05) in soil after immature manure, and slurry spraying, respectively. The estimated concentrations in the soil of fields of radish, leafy vegetables, tomato, and spring-seeded and autumn-seeded onions at harvest were −1.99 (95% CI: −2.48 to −1.57), −2.87 (95% CI: −3.36 to −2.42), −3.82 (95% CI: −4.32 to −3.40), −5.36 (95% CI: −5.85 to −4.93), and −5.94 (95% CI: −6.43 to −5.52) log10 CFU/g, respectively. The concentrations in the bodies of leafy green spinach and lettuce were −9.88 (95% CI: −10.38 to −9.43) and −10.91 (95% CI, −11.52 to −8.05) log10 CFU/g, respectively. The probability of ingesting bla-harboring E. coli of dairy origin with raw vegetables in Japan was thus assessed to be very low. One Health impact statement This study applied a release assessment in the World Organisation for Animal Health framework for antimicrobial resistance risk assessment to connect the antimicrobial use for dairy cattle, manure production and vegetable farming. As vegetable is often consumed raw, the assessment is directly associated with human health. Although the environmental continuum was not explored, the reduction of the hazard on the soil of vegetable farms was considered. The study involved the engagement with dairy and vegetable farmers and the agriculture industry in understanding farming behavior and value chain. The approach in this study can be applied to the complex problems across the animal-human-environment interface.